2017
DOI: 10.1111/nhs.12393
|View full text |Cite
|
Sign up to set email alerts
|

Scottish healthcare student's perceptions of an interprofessional ward simulation: An exploratory, descriptive study

Abstract: The most memorable learning occurs during placement. Simulated interprofessional learning is a logical learning opportunity to help healthcare professionals work beyond their professional silos. In this qualitative study, we investigated the perceived learning of students from six health professions (adult nursing, diagnostic radiography, occupational therapy, physiotherapy, dietetics, and pharmacy) from their participation in a 45 min interprofessional ward simulation. Semistructured focus groups were underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
3
16
0
2
Order By: Relevance
“…The responsibility of promoting interprofessional collaboration at mealtimes must also extend to educational institutions. Studies on interprofessional education typically involve health‐care professions, such as medicine, nursing, physiotherapy, occupational therapy, dietetics, and pharmacy (Hammick, Freeth, Koppel, Reeves, & Barr, ; McKenna et al, ; Roberts & Goodhand, ), with little attention paid to effective collaboration with support service personnel. The findings of the present study support previous reports that foodservice staff are integral to nutrition care through their role in meal preparation and delivery (Keller et al, ; Ottrey & Porter, ), thus should be considered part of the health‐care team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responsibility of promoting interprofessional collaboration at mealtimes must also extend to educational institutions. Studies on interprofessional education typically involve health‐care professions, such as medicine, nursing, physiotherapy, occupational therapy, dietetics, and pharmacy (Hammick, Freeth, Koppel, Reeves, & Barr, ; McKenna et al, ; Roberts & Goodhand, ), with little attention paid to effective collaboration with support service personnel. The findings of the present study support previous reports that foodservice staff are integral to nutrition care through their role in meal preparation and delivery (Keller et al, ; Ottrey & Porter, ), thus should be considered part of the health‐care team.…”
Section: Discussionmentioning
confidence: 99%
“…The responsibility of promoting interprofessional collaboration at mealtimes must also extend to educational institutions. Studies on interprofessional education typically involve health-care professions, such as medicine, nursing, physiotherapy, occupational therapy, dietetics, and pharmacy (Hammick, Freeth, Koppel, Reeves, & Barr, 2007;McKenna et al, 2014;Roberts & Goodhand, 2018), with little attention paid to effective collaboration with support service personnel.…”
Section: Discussionmentioning
confidence: 99%
“…The experiences obtained from interprofessional simulations have been mostly positive (Costello et al, 2018;Ivey, Bowman, & Lockeman, 2018;Jakobsen et al, 2018;Popkess et al, 2017;Roberts & Goodhand, 2018;Zamjahn et al, 2018), and there have been few differences in the participants' satisfaction levels based on different occupational groups or sectors. However, in a study by Jakobsen et al (2018), medical students were found to learn more than nursing students about the leader's role during a simulation.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The participants in interprofessional simulations have appreciated the related opportunity for learning in situations that resemble reality (Costello et al, 2018;Hovland, Whitford, & Niederriter, 2018;Naismith et al, 2020) and allow applying theory to practice (Hovland et al, 2018). Professional simulation training has supported the learning of high-quality care and the development of the learners' professional growth (Roberts & Goodhand, 2018). The participants have found that the simulations have increased their confidence in their own skills (Hovland et al, 2018;Jakobsen et al, 2018;Smith et al, 2018) and helped them prioritize patient needs (Roberts & Goodhand, 2018;Smith et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation